2015
DOI: 10.1021/acs.accounts.5b00165
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Association Processes Leading from a Silica Precursor to a Mesoporous SBA-15 Material

Abstract: During the last two decades, the synthesis of silica with an ordered mesoporous structure has been thoroughly explored. The basis of the synthesis is to let silica monomers polymerize in the presence of an amphiphilic template component. In the first studies, cationic surfactants were used as structure inducer. Later it was shown that pluronic copolymers also could have the role. One advantage with the pluronics copolymers is that they allow for a wider variation in the radius of pores in the resulting silica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 45 publications
0
30
1
2
Order By: Relevance
“…8(i)). The heat treatment performed at 550 • C promoted the complete removal of organic surfactants as well as the growth by self-assemble of several hexagonal mesoporous along the caxis [82]. This procedure resulted in the formation of SBA-15 mesoporous silica/TiO 2 nanocrystals (Fig.…”
Section: Transmission Electron Microscopy Images Analysesmentioning
confidence: 99%
“…8(i)). The heat treatment performed at 550 • C promoted the complete removal of organic surfactants as well as the growth by self-assemble of several hexagonal mesoporous along the caxis [82]. This procedure resulted in the formation of SBA-15 mesoporous silica/TiO 2 nanocrystals (Fig.…”
Section: Transmission Electron Microscopy Images Analysesmentioning
confidence: 99%
“…The properties of SBA-15 mesoporous materials have been studied for years by different authors, who reported the effect on the variables of synthesis on the corresponding structure and morphology developed [26][27][28][29]. For instance, Lee et al [30] studied the effect of temperature and stirring rate on the morphology of the material.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Another study suggests that the spherical micelles aggregate into flocs of spherical micelles and that these form cylindrical micelles that rearrange into the hexagonal structure. 18 However, the synthesis conditions have varied for the different studies, for example which surfactant and silica precursor that were used, reaction temperature etc. A correlation between the synthesis conditions and micellar evolution is also lacking.…”
Section: Introductionmentioning
confidence: 99%